Instrumented mouthguards in men's rugby league: quantifying the incidence and probability of head acceleration events at a group and individual level - Tooby, J.; Owen, C.; Sawczuk, T.; Roe, G.; Till, K.; Phillips, G.; Vishnubala, D.; White, R.; Rowson, S.; Tucker, R.; Tierney, G.; Jones, B. (Sports Medicine, 2025)
Background: There is growing concern that exposure to head acceleration events (HAEs) may be associated with long-term neurological effects. Objectives: To quantify the incidence and probability of HAEs during men`s professional rugby league match-play on a group and individual basis using instrumented mouthguards (iMGs). Methods: A total of 91 men`s professional rugby league players participating in the 2023 Super League season wore iMGs, resulting in the collection of 775 player matches (mean 8.3 matches per player). Incidence of HAEs (rate of HAEs per median playing time) was calculated via generalised linear mixed models. Probability of HAEs (likelihood of experiencing an HAE during a tackle-event) was calculated using an ordinal mixed effects regression model. Results: The mean incidence of HAEs exceeding 25 g per median playing time ranged from 0.86-1.88 for back positions and 1.83-2.02 for forward positions. The probability of exceeding 25 g during a tackle event was higher for ball-carriers (6.29%, 95% confidence intervals [CI] 5.27-7.58) than tacklers (4.26%, 95% CI 3.48-5.26). Several players exhibited considerably higher incidence and probability than others, e.g. one player averaged 5.02 HAEs exceeding 25 g per median playing time and another had a probability of 20.00% of exceeding 25 g during a tackle event as a ball-carrier and 34.78% as a tackler. Conclusions: This study quantifies the incidence and probability of HAEs in men`s rugby league match-play, advancing our understanding of HAE exposure in men`s rugby league. These findings support the development of individualised HAE mitigation strategies targeted at individuals with elevated HAE exposures.